(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The structure of hypereutectic aluminum-silicon alloys consists of primary silicon crystals arranged in a eutectic matrix. In the present work the influence of different types of modifiers on the size and shape of the silicon crystals in the composition of the eutectic of the AlSi18 alloy has been studied. The classic for this type of alloys modifier (phosphorus), as well as the nanomodifiers SiC and nanodiamonds (ND) have been used. The results of the microstructural analysis show that the three modifiers used affect differently the shape and size of the eutectic silicon of the investigated alloy.